The Conception of Man in K. Jaspers’ Philosophy - Repšys, Jonas (Problemos, 2014)
On the basis of an analysis of some fundamenlal works by K. Jaspers, the article deals with some general and distinguishing features of his philosophy. Attention is centred on a critical analysis of K. Jaspers’ conception of man. The article ends with discussion on methodological drawbacks of K. Jaspers’ existentialist anthropology as well as on the existentialist way of thought in general.